Building capacities for evidence and outcome-based food policy planning and implementation: The example of the Comprehensive Africa Agriculture Development Programme - Badiane, Ousmane; Odjo, Sunday P.; Ulimwengu, John M. (International Food Policy Research Institute, 2010)
The Comprehensive Africa Agriculture Development Programme (CAADP) is an Africawide framework for revitalizing agriculture and rural development in order to accelerate economic growth and progress toward poverty reduction and food and nutrition security. This study reviews CAADP and its strategic objectives, key players, implementation modalities, and approach to ensuring evidence and outcome-based policy planning and implementation. The study also lays out CAADP's common analytical framework at the country level and shares economic modeling results from member countries of the Economic Community of West African States (ECOWAS) in which analysis was conducted to examine agricultural growth and investment options for meeting CAADP growth and expenditure targets and the Millennium Development Goal target of halving poverty. Finally, the paper discusses CAADP's review and dialogue mechanisms and knowledge support systems that have been put in place to facilitate benchmarking, mutual learning, and capacity strengthening that will improve agricultural policy, program design, and implementation.